POTRET KEMISKINAN DALAM DIMENSI DAN KARAKTERISTIKNYA - Rahayu, Siti Aisyah Tri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
This papers aim to explain the poverty and policy, particularly in developing world. This article will try to analyze poverty and its measure, characteristics and policy to solve it. From the available data, we know that the poverty in Indonesia has been declined very dramatic until 1996, before the economic crisis. Through the crisis, there are a large number of people below poverty line is increase. However, poverty is always became a center of problem in macroeconomic that must be reduce to bring people to get welfare economics. And, there are many policies to solve the poverty problem that we can adopt to reduce poverty.